Investigating MRI‐Associated Biological Aspects of Racial Disparities in Prostate Cancer for African American and White Men - Zabihollahy, Fatemeh; Miao, Qi; Naim, Sohaib; Sonni, Ida; Vangala, Sitaram; Kim, Harrison; Hsu, William; Sisk, Anthony; Reiter, Robert; Raman, Steven S.; Sung, Kyunghyun (Journal of magnetic resonance imaging, 2025)
Background Understanding the characteristics of multiparametric MRI (mpMRI) in patients from different racial/ethnic backgrounds is important for reducing the observed gaps in clinical outcomes. Purpose To investigate the diagnostic performance of mpMRI and quantitative MRI parameters of prostate cancer (PCa) in African American (AA) and matched White (W) men. Study Type Retrospective. Subjects One hundred twenty‐nine patients (43 AA, 86 W) with histologically proven PCa who underwent mpMRI before radical prostatectomy. Field Strength/Sequence 3.0 T, T2‐weighted turbo spin echo imaging, a single‐shot spin‐echo EPI sequence diffusion‐weighted imaging, and a gradient echo sequence dynamic contrast‐enhanced MRI with an ultrafast 3D spoiled gradient‐echo sequence. Assessment The diagnostic performance of mpMRI in AA and W men was assessed using detection rates (DRs) and positive predictive values (PPVs) in zones defined by the PI‐RADS v2.1 prostate sector map. Quantitative MRI parameters, including Ktrans and ve of clinically significant (cs) PCa (Gleason score ≥ 7) tumors were compared between AA and W sub‐cohorts after matching age, prostate‐specific antigen (PSA), and prostate volume. Statistical Tests Weighted Pearson's chi‐square and Mann–Whitney U tests with a statistically significant level of 0.05 were used to examine differences in DR and PPV and to compare parameters between AA and matched W men, respectively. Results A total number of 264 PCa lesions were identified in the study cohort. The PPVs in the peripheral zone (PZ) and posterior prostate of mpMRI for csPCa lesions were significantly higher in AA men than in matched W men (87.8% vs. 68.1% in PZ, and 89.3% vs. 69.6% in posterior prostate). The Ktrans of index csPCa lesions in AA men was significantly higher than in W men (0.25 ± 0.12 vs. 0.20 ± 0.08 min−1; P < 0.01). Data Conclusion This study demonstrated race‐related differences in the diagnostic performances and quantitative MRI measures of csPCa that were not reflected in age, PSA, and prostate volume. Evidence Level 3 Technical Efficacy Stage 2